The application of positive psychology in English learning for students of MTsN 3 Sleman - Faraz Faraz; Dian Dwi Anisa; Dwiansari Ramadhani (Universitas Muhammadiyah Magelang, 2024)
This community service (PkM) aims to introduce the concept of Positive Psychology (PP) theory into English learning classroom to junior high school students. The method used is through direct teaching and training in the classroom over the course of four meetings. The teaching is carried out in several sessions consisting of material delivery on psychological factors of learning, easy steps to write, the application of positive psychology in relation to learning English, and the theory of writing in English. The teaching series was attended by grade 8 students at MTsN 3 Sleman whose English language skills were relatively low. The result obtained from this community service is that students can apply positive psychology theory in classroom by writing a gratitude journal as the main outcome.